2006
DOI: 10.2114/jpa2.25.331
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Insulation and Body Temperature Wearing a Thermal Swimsuit during Water Immersion

Abstract: This study evaluated the effects of a thermal swimsuit on body temperatures, thermoregulatory responses and thermal insulation during 60 min water immersion at rest. Ten healthy male subjects wearing either thermal swimsuits or normal swimsuits were immersed in water (26°C or 29°C). Esophageal temperature, skin temperatures and oxygen consumption were measured during the experiments. Metabolic heat production was calculated from oxygen consumption. Heat loss from skin to the water was calculated from the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Wearing thermal protection gear provides insulation but results in nonuniform and higher skin temperatures. Although there are apparently no differences in thermal sensation and shivering thermogenesis when T s decreases uniformly versus nonuniformly (wet suit covering trunk upper arms and legs), tissue insulation (vasoconstriction) was significantly higher when T s changes were nonuniform due to augmented cold sensory input form the periphery (404). It has also been noted that when T s were maintained at a higher level during cold immersion the temperature gradient between body and water actually increases and this may result in greater heat loss and decrease in core temperature (16,267,305).…”
Section: Head-out Water Immersion In Cold Watermentioning
confidence: 93%
See 1 more Smart Citation
“…Wearing thermal protection gear provides insulation but results in nonuniform and higher skin temperatures. Although there are apparently no differences in thermal sensation and shivering thermogenesis when T s decreases uniformly versus nonuniformly (wet suit covering trunk upper arms and legs), tissue insulation (vasoconstriction) was significantly higher when T s changes were nonuniform due to augmented cold sensory input form the periphery (404). It has also been noted that when T s were maintained at a higher level during cold immersion the temperature gradient between body and water actually increases and this may result in greater heat loss and decrease in core temperature (16,267,305).…”
Section: Head-out Water Immersion In Cold Watermentioning
confidence: 93%
“…This may be an issue with wet suits. Wearing a wet suit in cold water resulted in a higher esophageal temperature and attenuation of shivering and thus V O 2 did not increase as much due to the higher insulation (404).…”
Section: Head-out Water Immersion In Cold Watermentioning
confidence: 97%
“…In NUST condition, subjects wore a partial coverage wetsuit (PCWS, 206776-09; Footmark Co. Ltd., Japan) at 26°C water, which made skin temperature distribution higher at trunk and lower at limbs compared to UST condition. On the basis of the author's previous work using PCWS (Wakabayashi et al 2006a), the water temperature of the two conditions was set at 29°C for UST and 26°C for NUST, which resulted in a similar mean skin temperature for both the conditions. Additionally, the water temperature in UST condition was similar to the water temperature (28.4°C) in the previous research (Choi et al 2003), which brings about cold-induced shivering thermogenesis and vasoconstriction.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, the effect of a partial coverage wetsuit (PCWS; covering trunk region, upper arms, and thighs) during cool water immersion was examined (Wakabayashi et al 2005(Wakabayashi et al , 2006a(Wakabayashi et al , b, 2007, and their specific characteristics differing from full wetsuits were observed. The tissue insulation (I tissue ) with a PCWS was similar to the naked condition, while previous study reported that wearing wetsuits decreased I tissue (Kang et al 1983;Shiraki et al 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation